2006
DOI: 10.1002/fam.929
|View full text |Cite
|
Sign up to set email alerts
|

Prudent practices for the design and installation of heat‐producing devices near wood materials

Abstract: SUMMARYThe conditions required to cause ignition of solid wood materials under short-term heating are examined, and it is found that the appropriate ignition temperature applicable under these conditions is 2508C. It is then shown that ignition requirements are different if long-term heating is involved and that ignition can occur at exposure temperatures much lower than the ignition temperature pertinent to short-term heating. It is shown that hot surfaces of 778C or higher, if located for a long duration nex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
1
Order By: Relevance
“…Using detailed in-depth temperature measurements they showed that at radiant fluxes near the critical heat flux for smoldering ignition (7.5 kW/m 2 ), ignition occurs at depth within the charred portion of the wood sample. This contrasts with the interpretations of Boonmee and Quintiere [7,8] of smoldering ignition as a surface phenomenon and contrasts with the views of Babrauskas et al [3] that self-heating is not involved in short term (minutes to hours) heating to ignition of wood.…”
Section: Introductioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Using detailed in-depth temperature measurements they showed that at radiant fluxes near the critical heat flux for smoldering ignition (7.5 kW/m 2 ), ignition occurs at depth within the charred portion of the wood sample. This contrasts with the interpretations of Boonmee and Quintiere [7,8] of smoldering ignition as a surface phenomenon and contrasts with the views of Babrauskas et al [3] that self-heating is not involved in short term (minutes to hours) heating to ignition of wood.…”
Section: Introductioncontrasting
confidence: 77%
“…In a recent paper Babrauskas, Gray and Janssens [3] reviewed the old literature and anecdotal fire incidents and concluded that prolonged heating can reduce the ignition temperature of wood. No laboratory work was included in investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the ignition of wood is complicated since, not only can it ignite in either flaming or glowing mode due to short-term, external heating, but it is also a material susceptible to self-heating. The latter mode of ignition [22] can be encountered when a device such as a hot pipe provides long-term, low-temperature 1 heating.…”
Section: Ignition: a Century Of Research And An Assessment Of Our Curmentioning
confidence: 99%
“…The chemistry of drying oils is quite complex and a treatment based on F-K theory and currently available laboratory data does not capture the trends, since such an exercise predicts that roughly a 300-mm cube of material would be needed in a room-temperature environment, whereas a 25 g quantity has been empirically shown to suffice [1]. Another category of practical fires are the ones originating in wood members that have been heated for months or years by a steam pipe or similar hot object [22]. The process involves selfheating of wood, but, again, the simplified theory does not apply.…”
Section: Self-heatingmentioning
confidence: 99%